DINAMIKA MASYARAKAT DAN BUDAYA DALAM PENDIDIKAN ISLAM - Mukhtar Nuhung (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
This article addresses the issue of the dynamics of society and culture in Islamic education. The results of the discussion can be understood that the community is a large or small group, consisting of several people, who by themselves because they are classically related and influence each other. In the sociology approach, it is seen that humans as members of groups or communities (not as individuals who are separated from their class or society) interact with each other that give birth to culture. Culture is the result of human activity and inner creation (reason), such as beliefs, arts and customs. Customs are born through educational processes that occur in community interactions both formally and informally. Thus, humans are very closely related to culture, the relationship is inseparable. When one is separated from the other, each form disappears. Society is a place for culture, as well as a pile of land growing in a tree, if humans are taken as a sample then spirit as culture and humans as a society. Every human being has culture and culture, there are people. Both are dwitunggal, this is what forms socioculture.